Not so bad: avoidance and aversive discounting modulate threat appraisal in anterior cingulate and medial prefrontal cortex - Schlund, Michael W.; Brewer, Adam T.; Richman, David M.; Magee, Sandy K.; Dymond, Simon (Frontiers in Behavioral Neuroscience, 2015)
The dorsal anterior cingulate (adACC) and dorsal medial prefrontal cortex (dmPFC) play a central role in the discrimination and appraisal of threatening stimuli. Yet, little is known about what specific features of threatening situations recruit these regions and how avoidance may modulate appraisal and activation through prevention of aversive events. In this investigation, 30 healthy adults underwent functional neuroimaging while completing an avoidance task in which responses to an Avoidable CS+ threat prevented delivery of an aversive stimulus, but not to an Unavoidable CS+ threat. Extinction testing was also completed where CSs were presented without aversive stimulus delivery and an opportunity to avoid. The Avoidable CS+ relative to the Unavoidable CS+ was associated with reductions in ratings of negative valence, fear, and US expectancy and activation. Greater regional activation was consistently observed to the Unavoidable CS+ during avoidance, which declined during extinction. Individuals exhibiting greater aversive discounting—that is, those more avoidant of immediate monetary loss compared to a larger delayed loss—also displayed greater activation to the Unavoidable CS+, highlighting aversive discounting as a significant individual difference variable. These are the first results linking adACC/dmPFC reactivity to avoidance-based reductions of aversive events and modulation of activation by individual differences in aversive discounting.